Effectiveness of Supratarsal Triamcinolone Injection in Patients with Vernal Keratoconjunctivitis - Mubashir Rahman, Mir Ali Shah, Sher Akbar Khan, Tajbar khan (Pakistan Journal of Ophthalmology, 2015)
Purpose: To determine the efficacy of supratarsal injection of triamcinolone acetate amongst patients with vernal keratoconjunctivitis. Material and Methods: It was descriptive case series study conducted in the Department of Ophthalmology, Lady Reading Hospital Peshawar in 6 months from 6th February to 6th July, 2012. A total of 196 patients with vernal keratoconjunctivitis were subjected to supratarsal injection of triamcinolone acetate. To determine the effectiveness, all patients were followed after two weeks of supratarsal injection of triamcinolone acetate for the complete disappearance of papillae and those patients in whom there was complete disappearance of the papillae were followed for the next three months for recurrence of the papillae. Data was analyzed by Statistical Package for Social Sciences (SPSS) version 10.0 and presented in the form of tables and graphs. Results: There were total of 196 patients comprising of 130 (66.33%) males and 66 (33.67%) females with an overall mean age of 15.23 ± 5.79SD. Maximum patients i.e. 130 (66.33%) were from the age group of 11 to 20 years. The supratarsal triamcinolone acetate injection was effective in 170 (86.73%) patients including 123 (61.18%) males and 47 (27.65%) females. No recurrence of the papillae was noted in any of the patients when followed for further three months time. Conclusion: Supratarsal injection of Triamcinolone acetate is effective in vernal keratoconjunctivitis for complete disappearance of papillae. Key words: Vernal Keratoconjunctivitis; Supratarsal injection; Triamcinolone Acetate; Papillae.